Prophylactic Infusion Regimens in the Management of Hemophilia - Ljung, Rolf C. R. (Thrombosis and Haemostasis, 1999)
The goal of prophylactic treatment of hemophilia is to convert the severe form of the disorder into a milder form by administration of factors VIII or IX. The rationale behind this is that chronic arthropathy, the hallmark of hemophilia after repeated bleedings, is less frequent and less severe in moderate hemophilia (i.e., factor VIII or factor IX concentrations of 1% to 4% of normal) than in severe hemophilia (i.e., factor VIII/factor IX concentrations lower than 1% of normal).1 Keep in mind, however, that prophylactic treatment also provides protection from all other forms of hemorrhage that may occur spontaneously or as a result of trivial trauma in the untreated hemophilic child. Today, prophylactic treatment is available to only a few hemophilia patients in the world, although it is recommended by the World Health Organization (WHO) and the World Federation of Haemophilia (WFH): “Since the main goal is to prevent joint bleeding and its sequelae, prophylaxis should be considered optimal management for persons with severe hemophilia A or B (i.e., with basal factor VIII and/or factor IX levels <1% of normal). Treatment should be started at the age of 1-2 years and be continued indefinitely. Where prophylaxis is not feasible or appropriate, on-demand therapy should be given.”2 In the United States, the Medical and Scientific Advisory Council of the National Hemophilia Foundation has recommended that “prophylaxis should be considered the optimal therapy for children with severe hemophilia A or B.”3 The aim of this chapter is to discuss prophylactic infusion regimens in the management of hemophilia.